PENERAPAN TECHNOLOGY READINESS ACCEPTANCE MODEL (TRAM) DALAM MENGUKUR KESIAPAN DAN PENERIMAAN TEKNOLOGI CASHLESS - Priambodo, Wisnu; Munna, Aliyatul; Pratama, Dicky Yudha; Supriyanto, Aji (SOSCIED, 2024)
In the era of globalization and industrial revolution 4.0, information and communication technology (ICT) has created major changes, especially in financial transactions. This phenomenon has led to the emergence of cashless payment systems as the dominant trend, including in the education sector. Schools in Semarang, as part of their efforts to adapt to such developments, need to shift from traditional payment methods to cashless payment technologies to improve efficiency and convenience. This study aims to understand the acceptance of Cashless technology among school teachers and employees in Semarang using the Technology Readiness Acceptance Model (TRAM) approach. Through Structural Equation Modeling (SEM) analysis, the results show that insecurity plays a major role in influencing perceived ease of use. Although the insecurity factor did not have a significant effect, security also had a positive effect on users' assessment of the usability of Cashless technology.